PRODUKSI ANTISERUM DAN KAJIAN SEROLOGI CHRYSANTHEMUM B CARLAVIRUS (CVB) - I G.R.M. Temaja, G. Suastika S.H. Hidayat & U. Kartosuwondo . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2010)
Antiserum production and serological assay of Chrysanthemum B Carlavirus (CVB). Virus identification based on spesific reaction between antigen and antibody in serological assay has been widely applied as a tool for plant virus detection. The aims of this research is to produce antiserum of the CVB by guinea pig immunization using purified CVB of Cianjur isolate. The antiserum was used further for the serological test. Serological methods for detection of CVB were I-ELISA, TBIA, western blot and ISEM. The result showed that guinea pig immunization using 150 µg of purified virus was able to produce 10.75 ml of antiserum. The antiserum produced had high sensitivity for detection of CVB when examined by I-ELISA and TBIA. Besides its low cost, TBIA allows the samples to be blotted on the nitrocellulose membranes in the field and storage of the membranes for later processing in the laboratory. This feature makes it the metode of choice for large-scale CVB surveying.